2016
DOI: 10.1186/s40697-016-0107-8
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin for Uremic Pruritus in Hemodialysis Patients: A Qualitative Systematic Review

Abstract: Purpose of the reviewUremic pruritus (UP) is a common discomfort of dialysis-dependent end-stage renal disease. Some studies suggest a neuropathic cause of UP. Gabapentin, an anticonvulsant, has shown promising results as an emerging drug to treat this condition.ObjectiveAn updated qualitative systematic review was conducted to evaluate its efficacy and safety in hemodialysis patients.Source of informationOvid MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, Clinicaltrials.gov, and Google Schol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…A total of 17 journal articles were identified and assessed for eligibility. Nine were excluded because of the following reasons: one was a pilot study, two were reviews, two were retrospective studies, one was a protocol, one was a correspondence letter, and three were nonrandomized clinical trials (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 17 journal articles were identified and assessed for eligibility. Nine were excluded because of the following reasons: one was a pilot study, two were reviews, two were retrospective studies, one was a protocol, one was a correspondence letter, and three were nonrandomized clinical trials (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…53,[96][97][98] In a double-blind, crossover, RCT of 25 HD patients assigned to gabapentin 300 mg by mouth after dialysis or placebo, pruritus intensity significantly improved with gabapentin but not with placebo. 53 Similarly, in a double-blind, placebo-controlled trial of 34 HD …”
Section: Peripheral Neuropathy Treatmentmentioning
confidence: 99%
“…98 A recent qualitative systematic review of 7 studies evaluating gabapentin (179 participants) supported a trial of gabapentin for the treatment of CKD-aP refractory to antihistamines and/or emollients. 97 Pregabalin, a medication similar to gabapentin, may also improve CKD-aP 37,99 and may be particularly useful when patients are not able to tolerate gabapentin. 1,100 In a randomized, crossover trial, 50 HD patients were assigned to gabapentin 300 mg or pregabalin 75 mg daily.…”
mentioning
confidence: 99%
“…Four randomized, controlled trials of a total of 138 patients with severe pruritus have shown gabapentin to reduce itch by between 4.6 and 6.4 cm more than placebo on a 10-cm visual analog scale (8,9) (Supplemental Movie 2). Pregabalin (n=67) reduced itch severity by 4.6 cm more than placebo (n=57) and also improved sleep quality and health-related quality of life (10).…”
Section: Introductionmentioning
confidence: 99%